Agents to treat BRAF-mutant lung cancer - Jean G Bustamante Alvarez; Gregory A Otterson (BioExcel Publishing Ltd, 2019)
BRAF mutations are seen in up to 3.5-4% of the non-small cell lung cancer (NSCLC) patients. BRAF V600E mutations account for 50% of these cases, and the remaining BRAF mutations are non-V600E. The biologic behavior of BRAF-mutated lung tumors tends to be more aggressive and resistant to chemotherapy, but responses to tyrosine kinase inhibitors such as BRAF inhibitors with or without MEK inhibitors have provided another effective tool to attain better response rates when compared to cytotoxic chemotherapy. New strategies such as immunotherapy are becoming as well another option to treat in the second-line setting patients with BRAF-mutated NSCLC.